ARQUITECTURA Y PATRÓN DE ASENTAMIENTO EN EL INTERMEDIO TARDÍO. INVESTIGACIONES EN LA FRONTERA ESTE, NORTE Y NOROESTE DE LA COMUNIDAD DE CHACCCHAHUA, DISTRITO HUACCANA - APURÍMAC - Allende Joaquín, Daniel (2017)
The results of archaeological research conducted in the East, North and Northwest border Chaccchahua community, district Huaccana, Chincheros, Apurimac shown. It is, among other things, our goal, to show an alternative way to see the patterns of settlement during the Late Intermediate (1000 BC - 1400 BC), taking into account the location, architecture, spatial mobility, organization and especially the average resources - environmental present in this area. Moreover, giving a gateway to future discussions and comparisons with other sites present in neighboring areas, to find similarities and differences. We start with the premise: the prehistoric occupation in the East, North and Northwest Community Chaccchahua border is marked by fortified settlements, with the pattern of very particular settlement, a very strong spatial mobility and territorial control over 3 natural regions (river yunga, Quechua, suni and puna). It has been more than a dozen sites located in the upper parts or ridges of the hills, the intermediate parts and lower parts, with a continuous occupation from the training to the Inca coming with higher occupancy late intermission.